Persistent risk of vascular complications and efficacy of prolonged dual antiplatelet therapy after myocardial infarction - I. S. Yavelo («REMEDIUM GROUP» Ltd., 2022)
The article discusses data on the duration of risk retention and the main cause of vascular complications in patients with acute coronary syndrome. Preconditions for prolonged use of dual antiplatelet therapy after myocardial infarction are presented. The authors consider the results of a large, prospective, randomized, placebo-controlled, multinational PEGASUS-TIMI 54 study evaluating the efficacy and safety of the long-term use of acetylsalicylic acid combined with ticagrelor (P2Y12 platelet receptor blocker) in patients with a high risk of thrombotic complications of atherosclerosis in the period from 1 to 3 years after myocardial infarction. The article presents an analysis of optimal approaches to prolonged double antiplatelet therapy after myocardial infarction, taking into account the results of the PEGASUS-TIMI 54 study, which laid the foundation for current clinical guidelines. The PEGASUS-TIMI 54 study demonstrated the benefits of prolonged dual antiplatelet therapy for at least 4 years after myocardial infarction in patients with a high risk of atherothrombotic complications and confirmed the expediency to reduce the dose of ticagrelor from 90 to 60 mg twice daily for 1 year after the onset of the disease to ensure the best balance of efficacy and safety of treatment. The possibility of prolonging double antiplatelet therapy using a combination of ASA and ticagrelor at a dose of 60 mg twice daily for 1 year after myocardial infarction is provided for in the guidelines for medical use of ticagrelor and is enshrined in existing clinical guidelines. Presently, ticagrelor is the only P2Y12 platelet receptor inhibitor approved in the Russian Federation as an adjunct to ASA for the long-term prevention of atherothrombotic cardiovascular events.